The Islamic concept of Banu Qurayzah's breach of covenant and the ideas of Orientalist Bostom A Critical Review of Islamic and Jewish Laws in the Context of War: بنو قریظہ کی عہد شکنی کا اسلامی تصور اور مستشرق بوسٹم کے افکار کا اسلامی اور یہود ی قوانین حرب کے تناظر میں تنقیدی جائزہ - Dr. Gulzar Ali; Dr. Shahid Amin; Dr. Shah Hussain (Acta-Islamica, 2022)
Islam is the only savior religion of all humanity. The greatest desire of Islam is the attainment of prosperity and peace for humanity. It takes action against those who stand in its way. That is why in every age the people of falsehood have sided against Islam and the Prophet of Islam (PBUH). In this regard, Orientalists have opened a front against Islam. Andrew G. Boston and other Orientalists of this tribe (Judeo-Christians) are trying to prove that Islam is a bloody religion by narrating various incidents. Among them is the incident of Banu Quraiza which took place in the battle of Ahzab. This the incident in which the Jews were punished for their disobedience, but the punishment was in accordance with the teachings of the Torah; and moreover, they applied this decision to themselves. This incident will be reviewed in this research article.